Appropriation of digital knowledge in the training of Mexican normalist students - María Guadalupe Veytia Bucheli; Álvaro Artavia Medrano (Universidad de Guadalajara, 2023)
Digital knowledge constitutes knowledge, skills and attitudes related to the use of Information and Communication Technologies (ICT) in the educational field. The training of normalist teachers requires, as a graduation profile, to strengthen the development of digital knowledge that allows them to enrich the design, development and implementation of didactic situations and sequences with the use of ICT, not only from an instrumental level, but also from a didactic perspective. This research presents the results of a quantitative, non-experimental, descriptive study, whose objective was to diagnose the appropriation of digital knowledge in the formation of Mexican normalist students. The sample consisted of 505 Mexican normal students from the states of Chihuahua, Hidalgo and Tamaulipas, who were administered a questionnaire with a Likert-type scale with 36 items distributed in 7 dimensions. Among the main findings, digital knowledge was identified with a higher score for the use of messaging services, as well as the management of different types of sizes and fonts; the lowest scores were recorded in data analysis with specialized software and the development of blogs to communicate information.